Epithelial genetic muscarinic receptor 3 ablation induces sex-specific modulation of colonic intestinal progenitor cells and response to intestinal injury - Ragab, Mohab; Wieland, Jessica; Waldherr Avila de Melo, Caroline; Agibalova, Tatiana; Ermolova, Anastasia; Durner, Niklas; Hempel, Anneke; Heindl, Fabian; Maurer, H Carlo; Steiger, Katja; Janssen, Klaus-Peter; Tschurtschenthaler, Markus; et al. (Journal of Crohn's and colitis, 2025)
Abstract Background & Aims Epithelial muscarinic acetylcholine receptor subtype 3 (M3R) signaling modulates intestinal stem and progenitor cell function, yet its impact on colonic homeostasis remains unclear. Hence, this study explores the sex-specific effects of epithelial genetic M3R ablation and muscarinic receptor agonism on murine colonic Lgr5-EGFP+ progenitor cells and epithelial homeostasis. Methods Genetic ablation of M3R was achieved using Vil-Cre × M3R fl/fl mice. The effects on Lgr5-expressing progenitor cells, epithelial homeostasis, and response to intestinal injury were assessed, with attention to sex-specific differences. Effects of cholinergic and muscarinic agonism on epithelial cell homeostasis were evaluated employing murine and human colonoids. Results Genetic epithelial ablation of the M3R employing Vil-Cre × M3R fl/fl mice interestingly resulted in the prominent reduction in Lgr5-expressing progenitor cells in male tissues, contrasting an expansion of Lgr5-expressing cells in female colonic epithelia. This difference was abrogated in young female Vil-Cre × M3R fl/fl mice, which harbor reduced circulating sex hormone levels. Genetic M3R ablation further induced changes to epithelial differentiation. Importantly, male Vil-Cre × M3R fl/fl mice developed severe inflammation following induction of acute experimental colitis, which did almost not affect female Vil-Cre × M3R fl/fl mice. Moreover, sex-specific effects of modulations of cholinergic and muscarinic signaling on epithelial cells could be corroborated in murine and human colonoids. Conclusions Our data reveal sex differences in the modulation of intestinal, colonic epithelial cells by cholinergic, muscarinic signaling and highlight the potential for therapeutic strategies targeting cholinergic receptor signaling in colonic inflammatory diseases. Graphical Abstract Graphical Abstract